Physical characteristics associated with neck pain and injury in rugby union players - Snodgrass, S. J.; Osmotherly, P. G.; Reid, S. A.; Milburn, P. D.; Rivett, D. A. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Neck pain and injury are common in rugby union. Physical characteristics predisposing players to neck injury are largely unknown. This study aimed to determine physical characteristics associated with neck pain and injury in rugby union players. METHODS: Semi-professional rugby union players (N.=142) underwent pre-season measurements including cervical active range of motion (AROM), strength, sensorimotor proprioception (joint position error), and anthropometry. A structured interview established previous neck injury history, current symptoms, playing position, competition level, age, and years playing rugby. Team physiotherapists and player telephone interviews identified players sustaining a neck injury during the competitive season (defined as any reported neck pain or neck injury). T-tests or Mann-Whitney U tests determined differences between neck injured and non-injured players. Logistic regression determined factors associated with neck injury history and incidence. RESULTS: Sixty-five (46%) players reported a previous neck injury; 11 (8%) sustained a neck injury during the competitive season. Player age (OR 1.14, 95% CI 1.03-1.25, P=0.009) was associated with neck injury history. Pre-season lateral flexion AROM was less in players sustaining a neck injury or reporting neck pain during the season (median left 23.6°, IQR 21.8-26.2°; right 27.9°, 23.6-32.5°) than in other players (left 34.8°, 28.8-41.0°, P<0.01; right 39.1°, 28.9-48.1°, P=0.03). Lateral flexion AROM was associated with increased risk of neck pain or injury (OR 0.82, 95%CI 0.71-0.94, P=0.005). CONCLUSIONS: Decreased cervical lateral flexion AROM may contribute to neck injury risk in rugby union players. However, few physical characteristics predicted neck injury incidence, suggesting additional factors should be explored to determine injury risk.